The truth of memoir : how to write about yourself and others with honesty, emotion, and integrity - Cohen, Kerry, frey50 (Cincinnati, OH Writer's Digest Books, 2014)
Cohen provides insight and guidelines for depcting the characters who appear in your memoir with honesty and compassion. You'll learn to choose which details to include and which secrets to tell, how to render the people in your life artfully and fully on the page and what reactions you can expect from those you include in your work, as well as from readers and the media.
Keywords: Autobiography -- Authorship; Autobiography -- How to